ANALYSIS OF THE INFLUENCE OF USING WATER INJECT CHARGE WATER SYSTEM RELIABILITY PLTDG PESANGGARAN 200 MW - Gede Esa Agra Sumerta; I Wayan Arta Wijaya; I Gusti Ngurah Janardana (Sean Institute, 2023)
PLTDG Pesanggaran is a power generation unit that produces electricity using liquefied natural gas and high-speed diesel as backup fuel. One way to maintain the unit’s reliability is by using an additional cooling system to prevent derating. The system employs the water injection method to lower the charge air temperature. In its implementation, water injection utilises condensate water from the engine by injecting it into the charge air area, specifically the CAC drain. The water rises to a certain level in the manifold, allowing direct contact with the charged air to decrease its temperature. This research aims to reduce the charge air temperature influenced by ambient air during the daytime, enabling the PLTDG Pesanggaran unit to operate at its maximum load of 15.2 MW. The analytical method employed in this study is quantitative descriptive. The research findings confirm that water injection effectively maintains the charge air temperature within the range of T=47-48 °C. Based on these conditions, the daily load output savings amount to IDR 14,162 kWh, resulting in cost savings of IDR 58,885,596,000 per year for 12 post-high temperature CA events.